ANALYSIS OF INTERNATIONAL PASSENGERS’ SATISFACTION WITH THE AUTO GATE AT INTERNATIONAL AIRPORT - Andi Frianto Peranginangin; Sintong Jasa Bakti Manurung; Anjar Ariansyah Sejat; I Wayan Yogi Arta; Evita Helena Merentek (Journal of Airport Engineering Technology (JAET), 2026)
At Kualanamu International Airport, long queues at the immigration checkpoint prompted the adoption of the Auto Gate system for biometric self-service clearance. This study assessed the satisfaction level of 153 international passengers toward the Auto Gate and examined its effect on overall service quality. A descriptive quantitative approach was used, with questionnaires developed from the five SERVQUAL dimensions — tangibles, reliability, responsiveness, assurance, and empathy. Data were analyzed through descriptive statistics and simple linear regression. Results showed that passengers were generally satisfied across all five dimensions, with empathy receiving the highest rating. Simple linear regression confirmed a significant positive effect of Auto Gate usage on passenger satisfaction (R² = 0.616, p < 0.05), indicating that 61.6% of the variation in satisfaction is explained by Auto Gate usage.